2008
DOI: 10.1186/1476-511x-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Krill Oil on serum lipids of hyperlipidemic rats and human SW480 cells

Abstract: Background: Cardiovascular disease (CVD) and colon cancer incidence are known to be closely related to dietary factors. This article evaluated effects of krill oil (KO) on serum lipids of hyperlipidemia rats and human colon cancer cells (SW480). Serum lipids of rats fed with high fat diet (HFD) and different doses of KO were measured by automatic analyzer. Effect of KO on viability of cells was determined by methyl thiazolyl tetrazolium (MTT) assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…Krill oil also possesses 48 times higher antioxidant potency than fish oil on the basis of ORAC (oxygen radical absorption capacity) values as a result of containing various kinds of powerful antioxidants, such as vitamins E, A and D, astaxanthin, and canthaxanthin (Farooqui, 2009). A number of animal and human studies have suggested that krill oil has a variety of biological functions, including positive effects on cardiovascular disease, non-alcoholic fatty liver disease, metabolic syndrome, premenstrual syndrome, endocannabinoids, inflammation, colon cancer and attention deficit hyperactivity disorder (Batetta et al, 2009;Bunea, El Farrah, & Deutsch, 2004;Deutsch, 2007;Ierna, Kerr, Scales, Berge, & Griinari, 2010;Sampalis et al, 2003;Vigerust et al, 2013;Zhu, Shi, Qian, Cai, & Li, 2008). It is possible that the proposed benefits of krill oil might arise from the synergism between EPA, DHA, phospholipids, astaxanthin and other bioactive constituents like vitamins and flavonoids.…”
Section: Introductionmentioning
confidence: 95%
“…Krill oil also possesses 48 times higher antioxidant potency than fish oil on the basis of ORAC (oxygen radical absorption capacity) values as a result of containing various kinds of powerful antioxidants, such as vitamins E, A and D, astaxanthin, and canthaxanthin (Farooqui, 2009). A number of animal and human studies have suggested that krill oil has a variety of biological functions, including positive effects on cardiovascular disease, non-alcoholic fatty liver disease, metabolic syndrome, premenstrual syndrome, endocannabinoids, inflammation, colon cancer and attention deficit hyperactivity disorder (Batetta et al, 2009;Bunea, El Farrah, & Deutsch, 2004;Deutsch, 2007;Ierna, Kerr, Scales, Berge, & Griinari, 2010;Sampalis et al, 2003;Vigerust et al, 2013;Zhu, Shi, Qian, Cai, & Li, 2008). It is possible that the proposed benefits of krill oil might arise from the synergism between EPA, DHA, phospholipids, astaxanthin and other bioactive constituents like vitamins and flavonoids.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, there are also astaxanthin, tocopherols, vitamin A, and other active substances in krill, which can further improve the economic value (Xie et al, ). Some studies have shown that Antarctic krill oil could inhibit fatty liver and had the activity of reducing blood lipids and blood sugar (Ferramosca et al, ; Tandy et al, ; Zhu, Shi, Qian, Cai, & LI, ).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 An increasing number of animal and human studies have provided evidence for the safety and efficacy of krill oil for managing conditions associated with chronic inflammation, 12,13 including dyslipidemia. 14,15 Despite krill oil's potentially superior toxicity profile in adults infected with HIV, compared to statins, to date, no studies have been conducted on the effects of krill oil for reducing HIV-related chronic inflammation. Therefore, the aim of this study was to collect preliminary data on the safety of krill oil in clinically stable adults who have HIV with evidence of systemic inflammation, and to estimate effect sizes for modulating soluble inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…One potential option is krill oil, a rich source of omega-3 fatty acids that has been shown to reduce inflammation 12,13 and normalize dyslipidemia. 14,15 Krill oil is extracted from the Antarctic krill crustacean (aquatic invertebrate Euphausia superba) and has potential advantages as an anti-inflammatory treatment, compared to fish oil, for which effectiveness has been well-studied in general populations. 16 Krill oil contains the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in phospholipids rather than in triacylglycerols, resulting in greater bioavailability.…”
Section: Introductionmentioning
confidence: 99%